Flame-Made Pt-Loaded TiO2 Thin Films and Their Application as H2 Gas Sensors. (26th November 2013) - Chomkitichai, Weerasak; Ninsonthi, Hathaithip; Liewhiran, Chaikarn; Wisitsoraat, Anurat; Sriwichai, Saengrawee; Phanichphant, Sukon
Abstract : The hydrogen gas sensors were developed successfully using flame-made platinum-loaded titanium dioxide (Pt-loaded TiO2 ) nanoparticles as the sensing materials. Pt-loaded TiO2 thin films were prepared by spin-coating technique onto Al2 O3 substrates interdigitated with Au electrodes. Structural and gas-sensing characteristics were examined by using scanning electron microscopy (SEM) and showed surface morphology of the deposited film. X-ray diffraction (XRD) patterns can be confirmed to be the anatase and rutile phases of TiO2 . High-resolution transmission electron microscopy (HRTEM) showed that Pt nanoparticles deposited on larger TiO2 nanoparticles. TiO2 films loaded with Pt nanoparticles were used as conductometric sensors for the detection of H2 . The gas sensing of H2 was studied at the operating temperatures of 300, 350, and 400°C in dry air. It was found that 2.00 mol% Pt-loaded TiO2 sensing films showed higher response towards H2 gas than the unloaded film. In addition, the responses of Pt-loaded TiO2 films at all operating temperatures were higher than that of unloaded TiO2 film. The response increased and the response time decreased with increasing of H2 concentrations.